PERBANDINGAN MANAJEMEN ASN DINEGARA KOREA SELATAN DAN NEGARA INDONESIA - Muslimatul Fauziyah; Aminullah (As-Sulthan Journal of Education, 2026)
Demands for improved quality of public services that are fast, responsive, and accountable are growing stronger with the development of the digital transformation era. In this context, the State Civil Apparatus (ASN) management system plays a strategic role as the main foundation of bureaucratic reform. South Korea is often cited as a benchmark for successful public administration reform due to its ability to build an efficient, performance-based ASN management system integrated with the use of technology. Conversely, although Indonesia has a strong regulatory framework through Law Number 5 of 2014 concerning ASN, the implementation of this policy still faces various challenges, particularly related to the application of meritocratic principles, objectivity in performance assessments, and consistency in ASN career development. This study aims to comparatively analyze the ASN management systems in South Korea and Indonesia by examining aspects of recruitment, career development, performance assessments, reward systems, and the influence of cultural and political factors on their implementation. The research approach used is a qualitative comparative study through literature analysis of relevant regulations, policy reports, and previous research findings. The study's findings indicate that the success of the South Korean civil servant management system is determined not only by performance-based policy design, but also by consistent implementation, an organizational culture that supports professionalism, and strict oversight mechanisms. Meanwhile, Indonesia still faces a gap between normative policies and field practices. This research is expected to provide theoretical and practical contributions to the development of civil servant management policies in Indonesia by identifying practices that can, in principle, be contextually adapted from South Korea. The findings are expected to serve as a reference in accelerating the realization of a professional, high-integrity, high-performance, and service-oriented Indonesian bureaucracy.